2019
DOI: 10.1021/jacs.9b00018
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Secondary Growth of Highly b-Oriented MFI Zeolite Films from Anhydrous Synthetic Powder

Abstract: Up to date, zeolite films have been mainly fabricated by in situ crystallization, secondary growth in a solution/hydrogel, or occasionally by vapor phase transformation of dry gel. Here we demonstrate for the first time a solvent-free secondary growth method for b-oriented silica MFI zeolite films using the synthetic powder from ground anhydrous raw solids in the presence of NH4F. Typically, precisely b-oriented MFI zeolite films are synthesized from seed layers of highly b-oriented MFI zeolite crystals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In contrast, developing facile synthetic methods enabling precise control over layer thickness remained largely unexplored. It has been reported that twin-free b-oriented MFI layers with sub-100-nm thickness could be obtained by using the dry gel conversion (20,36) or gel-less method (24,37); nevertheless, it was unclear whether the commonly used solution-based epitaxial growth method could be used for fabricating sub-100-nm-thick b-oriented MFI layers.…”
Section: Synthesis Of B-oriented Ultrathin Mfi Layersmentioning
confidence: 99%
“…In contrast, developing facile synthetic methods enabling precise control over layer thickness remained largely unexplored. It has been reported that twin-free b-oriented MFI layers with sub-100-nm thickness could be obtained by using the dry gel conversion (20,36) or gel-less method (24,37); nevertheless, it was unclear whether the commonly used solution-based epitaxial growth method could be used for fabricating sub-100-nm-thick b-oriented MFI layers.…”
Section: Synthesis Of B-oriented Ultrathin Mfi Layersmentioning
confidence: 99%
“…Recent decades have witnessed great efforts on the preparation of b ‐oriented MFI films with few twins . Diverse methods like multi‐mode microwave heating, precursor solution pretreatment, employing specifically designed template ( trimer ‐TPAOH), vapor phase transformation, solvent‐free epitaxial growth and additive addition (like ammonia salts, sodium tungstate and 1,2‐dihydroxybenzene) have proven effective for twin suppression.…”
Section: Figurementioning
confidence: 99%
“…Normally, oriented membranes display superior separation performances in comparison with randomly oriented ones because a perfect orientation often results in a reduction of intercrystalline defects and transport pathways, which is helpful to enhance the selectivity and permeance. Therefore, much effort has been paid on the preparation of oriented molecular sieve membranes [25–34] …”
Section: Figurementioning
confidence: 99%
“…Further, it should be noted that the presence of synthesis building blocks (Zn 2+ and cbIM) in the colloidal suspension of ZIF‐95 seeds is necessary for the formation of a dense ZIF‐95 membrane through epitaxial growth. As shown in Figure S12, the ZIF‐95 seed crystals can still grow together and then form a rather continuous and oriented ZIF‐95 membrane layer through vapor‐assisted in‐plane epitaxial growth, but observable gaps still exist if the synthesis building blocks Zn 2+ and cbIM were not added to the colloidal suspension of the ZIF‐95 seeds during vacuum filtration, which can be attributed to an insufficient concentration of precursor nutrients for secondary growth for a dense ZIF‐95 membrane [34] …”
Section: Figurementioning
confidence: 99%